2006
DOI: 10.1038/sj.onc.1209905
|View full text |Cite|
|
Sign up to set email alerts
|

Disruption of the retinoblastoma pathway by small interfering RNA and ectopic expression of the catalytic subunit of telomerase lead to immortalization of human ovarian surface epithelial cells

Abstract: The risk of developing ovarian cancer is about 1% over a lifetime, but it is the most deadly gynecologic cancer, in part due to lack of diagnostic markers for early-stage disease and cell model system for studying early neoplastic changes. Most existing immortal human ovarian surface epithelial cells were achieved by using viral protein such as SV40 T/t antigen or E6/E7, which inactivate multiple cellular pathways. In the current study, we used a small interfering RNA (siRNA) against the retinoblastoma gene (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…Earlier studies have shown immortalization of human epithelial cells through disruption of pRb and/or p53 function in combination with overexpression of hTERT (Whitaker et al, 1995;Hahn, 2002;Yang et al, 2006). However, we and others have described earlier that the only step required for the immortalization of somatic cells is activation of telomerase (Jiang et al, 1999;Morales et al, 1999;Li et al, 2007).…”
mentioning
confidence: 76%
“…Earlier studies have shown immortalization of human epithelial cells through disruption of pRb and/or p53 function in combination with overexpression of hTERT (Whitaker et al, 1995;Hahn, 2002;Yang et al, 2006). However, we and others have described earlier that the only step required for the immortalization of somatic cells is activation of telomerase (Jiang et al, 1999;Morales et al, 1999;Li et al, 2007).…”
mentioning
confidence: 76%
“…To establish whether a single disruption of either the p53 or RB1 pathway would promote telomerase-induced human OSE cell immortalization, Liu et al used RNAi technology to knock down either RB1 or p53 in combination with ectopic expression of the TERT in human OSE cells. Significantly, knockdown of either RB1 (Yang et al 2007a) or p53 (Yang et al 2007b) in the presence of TERT is sufficient to immortalize human OES cells. It was later shown that human OSE cells could be immortalized by TERT expression without functional disruption of RB1 and p53 (Li et al 2007).…”
Section: Reactivation Of Telomerase In Ose and The Role In Ovarian Rementioning
confidence: 97%
“…Thus, while telomerase activity is indispensable in the immortalization step of human OSE, p53 and RB1 are not, at least under certain conditions. Furthermore, TERT-immortalized human OSE cells have lengthened telomeres, are diploid without chromosomal instability, and maintain epithelial characters without tumorigenicity (Kusakari et al 2003, Yang et al 2007a, 2007b, Sasaki et al 2009). …”
Section: Reactivation Of Telomerase In Ose and The Role In Ovarian Rementioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this limitation, we generated a second-generation model of immortalized, nontumorigenic cells by using retrovirus-mediated small-interfering RNA against p53 or Rb, in combination with the ectopic hTERT expression (124125). This new model offers new opportunities to study the mechanisms underlying development of different types and grades of ovarian cancer and to define the number and combinations of genetic changes required for ovarian carcinogenesis.…”
Section: Models Of Ovarian Cancermentioning
confidence: 99%